Patient parameters and response after administration of rituximab in pediatric mature B‐cell non‐Hodgkin lymphoma. Issue 4 (22nd December 2021) - Bethke, Maria; Varga, Georg; Weinhage, Toni; Sabharwal, Harshana; Mellgren, Karin; Randau, Gerrit; Rolfing, Meike; Wittkowski, Helmut; Foell, Dirk; Michgehl, Ulf; Burkhardt, Birgit
Abstract: Background: Mature aggressive B‐cell lymphomas are heterogenous malignancies that make up more than half of all diagnosed non‐Hodgkin lymphoma in children and adolescents. The overall survival rate increased over the last decades to 80%–90% due to fine tuning of polychemotherapy. However, new therapeutic implications are needed to further increase the overall survival. Current clinical trials analyze the therapeutic effect of rituximab in pediatric patients, while the mechanism of action in vivo is still not fully understood. Methods: Effector molecules important for tumor defense were analyzed before and at day 5 after rituximab treatment via flow cytometry. Serum rituximab levels were measured with an ELISA. Results: We evaluated patient parameters that may affect treatment response in relation to rituximab administration and serum rituximab levels. We indeed found a reduction of Fcγ receptor (FcγR) II levels after rituximab treatment in monocyte subtypes, whereas FcγRI expression was significantly increased. Serum levels of proinflammatory marker proteins S100A8/A9 and S100A12 significantly decreased after treatment to normal levels from an overall proinflammatory state before treatment. CD57, perforin, and granzyme B expression decreased after treatment, comprising a less cytolytic natural killer (NK) cell population. Conclusion: The highlighted effects of rituximab treatment on patient's immune response help in understanding the biology behind tumor defense mechanisms and effector function. After subsequent studies, these novel insights might be translated into patient care and could contribute to improve treatment of pediatric patients with mature aggressive B‐cell lymphoma.